SISTEM INFORMASI ORDER JASA PARIWISATA (STUDY KASUS : MUSA TOUR LAMPUNG) - Andre Andre; agung tri prastowo (Jurnal Teknologi dan Sistem Informasi, 2020)
Musa Tour Lampung is a company engaged in the field of tour services and tourism trevel, the problem with Musa Tour Lampung is managing data on booking tour services that are still done manually, which is recorded in the bus book and will be prescribed using the ms excel application, and there is no information if it occurs the similarity of data, and the absence of periodic booking reports in accordance with what is needed by Musa Tour Lampung. The system development method uses the waterfall method and the system design uses the UML system design. So that this study is not subjective, the authors also use research methods in the form of observations, interviews, documentation in processing tourism booking data.The result achieved is a tourism tour service system to increase the range of bookings owned by the company in listings, so Musa Tours Lampung wants to build a web-based booking facility using, focused on managing booking data so that it can generate reports that are needed by the company.. Keywords: Tourism Services Order Information System, Waterfall, UML